Cryptocurrencies its Impact and Recognition - Jessica Padilla; Johana Molina Galeano; Marcela Amaya; Orlando Carmelo Castellanos Polo (International Journal of Integrative Research, 2023)
The objective of this research article is to publicize the emergence of cryptocurrencies and their origins, thus knowing the impact that different currencies are having in the commercial, financial and economic fields through investments, and to know a little about their recognition. We will also mention the different digital currencies or also called cryptocurrencies or cryptocurrencies most used from the moment the purchase begins until the result is obtained, analyzing whether this has a positive or negative impact on the market and how it behaves, as well as the different types of investments and wallets that have emerged over time. In order to understand the economic and financial impact of digital currencies in the economy, different bibliographies related to the trajectory and effect of cryptocurrencies were read, analyzed and filtered, tables were also made and graphs were studied to know the financial behavior through digital currencies. Every day there are more investors interested in learning about these. Its economic results are very diverse depending on the period and how it is coupled with financial institutions, its value remains up and down, it is not something stable. Their legality or not has not yet been decided since it is legal, that is to say that no law prohibits or protects or regulates them. It is concluded that per day, there are more companies interested and that accept cryptocurrencies to obtain their benefits, this investment method is increasingly used. Bogotá is positioned as the city in Colombia that carries out transactions with these crypto assets the most, although the list of users is still small and investors are few. This type of transaction has caused a new practical revolution in the local market, allowing various national and international economic functions to be carried out  this favors the expansion of transactions geographically.